Written evidence of the inimitability of the Quran on comprehending the concept of Arabic linguistic history and theology - Yaacob, Solehah@Nik Najah Fadilah (Medcraveonline, 2020)
The study focuses on how the relationship between Arabic linguistic and theology concept in the Quran will enhance the understanding of Islamic principles. However, there have been too many pointless debates and discussions on the issue of influence of Arabic linguistic on philosophical theology. In order to highlight significant issues of the Quranic interpretation of the theology as a consummation of metaphysics or Tauhidic concept, the need of understanding of deep semantic approach is necessary. In this study, the Tauhidic concept is presented not to linguists but theologians (Mu`tazilah) in impressing upon them the need to study not only theology but also grammar and literary theory in order to improve the understanding of the inimitability of the Qur’an. An analytical discussion on some views among the scholars on the topic is a method approach of the research.